Observed Parent Behaviors as Time-Varying Moderators of Problem Behaviors Following Traumatic Brain Injury in Young Children - Treble-Barna, Amery (Dev Psychol, 2016)
Parent behaviors moderate the adverse consequences of pediatric traumatic brain injury (TBI); however, it is unknown how these moderating effects change over time. This study examined the moderating effect of observed parent behaviors over time since injury on the relation between TBI and behavioral outcomes. Participants included children, ages 3–7 years, hospitalized for moderate (n = 52) or severe (n = 20) TBI or orthopedic injury (OI; n = 95). Parent–child dyads were videotaped during structured task and free play conditions and parents completed child behavior ratings. Linear mixed models using a lagged, time-varying moderator analysis examined the relationship of observed parent behaviors at the baseline, 6-month, and 12-month assessments to child behavior problems at 6 months, 12 months, and 18 months post injury, after controlling for pre-injury levels of child behavior problems. The effect of TBI on behavior was exacerbated by less favorable parent behaviors, and buffered by more favorable parent behaviors, in children with severe TBI over the first 12 months post injury. By 18 months post injury, however, the moderating effect of parent behaviors diminished such that children with severe TBI showed more behavior problems relative to children with moderate TBI or OI regardless of parent behaviors or in response to parent behaviors that were initially protective. The results suggest that the moderating effects of the family environment are complex and likely vary in relation to both recovery and developmental factors, with potentially important implications for targets and timing of intervention.